ANALISIS DIVIDEND PAYOUT RATIO (DPR), EARNING PER SHARE (EPS) DAN FINANCIAL LEVERAGE (FL) TERHADAP HARGA SAHAM - Zelia Alexandrina de Oliveira Lobo, 09.05.52.0051; Sudarsi, Sri (Students' Journal of Accounting and Banking, 2016)
This study aimes to examine and analyze the effect of Dividend Payout Ratio (DPR), Earnings Per Share(EPS) and Financial Leverage(FL) on stock prices. The research methods used are descriptive and verificative.Methods of analysis used are multiple linear regression,correlation and coefficient of determination. Simultaneous hypothese  is tested  through F test and partial hypotheses are tested trough t test. Annual data are obtained from the Indonesia Stock  Exchange. The sampling method in this study using purposive sampling method with the research period 2010 to 2013. The data used in this study is data from 14 manufacturing companies that mean the selection criteria. The analytical method used in this research is multiple regression analysis. The research purpose that DPR negative and significant on stock price, EPS negative partially did not significantly affect on stock price, and FLsignificant positive on stock price.  Keywords: Stock Price, Dividend Payout Ratio, Earnings Per Share, Financial Leverage